Kratom – vom natürlichen Heilmittel zur Suchtdroge und zurück - Müller, Christian P.; Yang, Yuting; Singh, Darshan; Lenz, Bernd; Müller, Elisabeth (Der Nervenarzt, 2024)
Background: Kratom/ketum is a psychoactive herbal preparation that has been used for a long time as a remedy and performance-enhancing substance in Southeast Asia. The advancement of globalization is making kratom increasingly more available in the western world, where it is becoming increasingly more used. Objective: The current research on kratom and its ingredients is presented. Material and methods: An overview of the use and effects of kratom is exemplary given on the basis of reports. The instrumentalization of the drug and its consequences up to the development of addiction are discussed. Results: Consumption is accompanied by several instrumentalizeable effects so that kratom is used as a therapeutic substance in the self-management of pain, anxiety and depression as well as other substance addictions. Another benefit comes from the performance-enhancing effects on physical work and in a social context. Consumption is usually well controlled, rarely escalates and has few and mostly mild aversive side effects. The danger arises from consumption particularly when there is an escalation of the dose and from mixed consumption with other psychoactive substances. The main alkaloid mitragynine and the more potent 7‑hydroxy-mitragynine are considered mainly responsible for the effect. Both have a complex pharmacology that involves partial µ‑opioid receptor agonism. Discussion: Epidemiological, clinical and neurochemical studies have shown that kratom only has a limited addictive drug profile, which might suggest a medical use as a remedy or substitute in addiction treatment.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Addiction; Enhanced performance; Instrumentalization; Ketum; Mitragynine